Implementation of a Postpartum Hemorrhage Safety Bundle at an Urban Safety-Net Hospital - Naima T. Joseph; Nikkia H. Worrell; Janice Collins; Melanie Schmidt; Grace Sobers; Kathlyn Hutchins; E. Britton Chahine; Christine Faya; Luanne Lewis; Victoria L. Green; Penny Z. Castellano; Michael K. Lindsay (Thieme Medical Publishers, Inc., 2020)
Background Postpartum hemorrhage (PPH) is a leading cause of preventable maternal morbidity and mortality. Standardized response to obstetric hemorrhage is associated with significant improvement in maternal outcomes, yet implementation can be challenging. Objective The primary objective is to describe the methodology for program implementation of the Alliance for Innovation on Maternal Health Safety Bundle on PPH at an urban safety-net hospital. Methods Over an 18-month period, interventions geared toward (1) risk assessment and stratification, (2) hemorrhage identification and management, (3) team communication and simulation, and (4) debriefs and case review were implemented. Hemorrhage risk assessment stratification rates were tracked overtime as an early measure of bundle compliance. Results Hemorrhage risk assessment stratification rates improved to >90% during bundle implementation. Conclusion Keys to implementation included multidisciplinary stakeholder commitment, stepwise and iterative approach, and parallel systems for monitoring and evaluation Implementation of a PPH safety bundle is feasible in a resource-constrained setting.